AN APPLICATION OF MEDICAL DIAGNOSIS USING INTUITIONISTIC FUZZY TREE AUTOMATA - A. Uma; S. Jayalakshmi (Utilitas Mathematica, 2025)
This paper is inspired by the Intuitionistic fuzzy Medical diagnosis that involves intuitionistic fuzzy relation, a new approach is proposed as the intuitionistic fuzzy tree automata to using the application of Medical diagnosis.